If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 4x + -12 Reorder the terms: 5x = -12 + 4x Solving 5x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = -12 + 4x + -4x Combine like terms: 5x + -4x = 1x 1x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 1x = -12 + 0 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| x-(-130)=102 | | 2x+3=4x-42 | | y=x+x^2-3 | | 6.5p+6.2=-12.36+4.9p | | (d+4)(d+4)=4 | | 5x^2+24x-20=0 | | 97=87+b | | .3(x+15)+.04(x+25)=25 | | 5(2-3x)=21 | | (d+4)=4 | | 4=a-4-3a | | 6x-7=4x-7 | | 126=w+38 | | -x^2+41x-180=0 | | 5-7(6x+2)=4 | | -5x+2=4x+29 | | 13x-3=13x+11x | | 400SA=1050 | | 1X+17=7x+29 | | x=-9x^2+42x+10 | | U=2(7n+30)+5(n+1) | | 967=16t^2 | | 3x+9-8x+5= | | 6x-(2x-4)=28 | | 7x^2-3x=x^2-20x+45 | | x^2+y^2+4x-8y-80=0 | | 2x-y=3x-y | | 1.79*3.6= | | X+3(5)=7 | | 4x^2y-y=0 | | 2x-36=64 | | c+16=41 |